2003
DOI: 10.1194/jlr.c200019-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of hexadecanoic acid to hexadecenoic acid by rat Δ6-desaturase

Abstract: A higher content of C16:1 n-10 has recently been reported in the preputial gland of mice with a targeted disruption of the gene encoding stearoyl-CoA desaturase 1 (SCD1 ؊ / ؊ mice) when compared with wild-type mice. This result has provided the first physiological evidence for the presence and regulation of a palmitoyl-CoA ⌬ 6-desaturase in mammals. To investigate the putative involvement of the known ⌬ 6-desaturase (FADS2) in this process, COS-7 cells expressing rat ⌬ 6-desaturase were incubated with C16:0. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…1 and data not shown). These results are in accordance with previous studies that have used this recombinant model to demonstrate the surprising diversity of ⌬ 6-desaturase substrates ( 34 ), including the conversion of 24:5 n-3 into 24:6 n-3, 24:4 n-6 into 24:5 n-6 ( 24 ), and 16:0 into 16:1 n-10 ( 29 ).…”
Section: Biosynthesis Of the Suspected Trans 11 Cis 13-cla In Rat Hesupporting
confidence: 82%
See 2 more Smart Citations
“…1 and data not shown). These results are in accordance with previous studies that have used this recombinant model to demonstrate the surprising diversity of ⌬ 6-desaturase substrates ( 34 ), including the conversion of 24:5 n-3 into 24:6 n-3, 24:4 n-6 into 24:5 n-6 ( 24 ), and 16:0 into 16:1 n-10 ( 29 ).…”
Section: Biosynthesis Of the Suspected Trans 11 Cis 13-cla In Rat Hesupporting
confidence: 82%
“…1C ). These results validated that our recombinant model was consistent with the known in vivo ⌬ 5-and ⌬ 6-desaturase activities and FA substrates of FADS1 and FADS2 ( 24,29 ) and showed that FADS3 was not functionally redundant with FADS1 and FADS2. Similar experiments carried out with saturated FA (12:0, 14:0, 16:0, and 18:0) also showed that FADS3 displayed no ⌬ 9-desaturase activity (data not shown).…”
Section: Downloaded Fromsupporting
confidence: 74%
See 1 more Smart Citation
“…Human and rat fatty acid desaturase 2 (FADS2) -encoding delta 6-desaturases recognize a saturated fatty acid as a substrate under some conditions (Ge et al, 2003;Guillou et al, 2003), and a human delta 6-desaturase gene has been reported to be expressed only in the sebaceous gland. Regarding microbial delta 6-desaturases, industrial producers of unsaturated fatty acids have focused mainly on fungi of the Mortierella spp., especially Mortierella alpina and Mortierella cincinelloides.…”
Section: Review Of Desaturase Studiesmentioning
confidence: 99%
“…The histidine residue is indispensable for electron transfer from NADH-dependent cytochrome b 5 reductase during the redox reaction ( 5, 6 ). Both this motif and that of diffused cytochrome b 5 are necessary to fully express desaturase activity ( 7,8 ). The other hydrophilic regions contain three histidine clusters (HX 3-4 H, HX 2-3 HH, and QX 2-3 HH) that form a catalytic center by coordinating nonheme diiron centers, and all of these histidine residues and the glutamine residue are essential for enzymatic activity ( 9, 10 ).…”
mentioning
confidence: 99%